Employee Engagement and Performance among Sales and Marketing Employees at The Ritz-Carlton Jakarta Pacific Place - Fauzan Ihza; Feri Ferdian (Journal of Multidimensional Management, 2026)
This study examines the relationship between employee engagement and self-reported performance among sales and marketing employees at The Ritz-Carlton Jakarta Pacific Place. A quantitative cross-sectional causal-associative survey used a census of all 34 employees. Employee engagement was measured through vigor, dedication, and absorption, while employee performance covered work quality, quantity, timeliness, and independence. Employee engagement achieved 81.23% of the ideal score and employee performance 91.94%. Dedication and absorption were rated more strongly than vigor, while performance dimensions were consistently high. A mathematical consistency check of the archived regression values indicates a positive but statistically non-significant relationship (B = 0.483, SE = 0.304, t = 1.589, F = 2.525, p approximately 0.122, R approximately 0.270, R-squared approximately 0.073). These reconciled values are consistent with the reported ANOVA sums of squares but should be confirmed against the original SPSS output before final publication. The findings suggest that management should prioritize employee energy and recovery, particularly the vigor dimension, while maintaining dedication and concentration through supportive leadership, realistic targets, recognition, and adequate job resources.